(untitled) (Herald of Journalism, 2019)
The author analyzes the place and role of modern national television journalism in the national information space in the context of the functions of television journalism. In this regard, he emphasizes that the most important factor in the function of television journalism is the study of the target audience. The viewer considers the feedback form as a unique way to communicate with the audience. The need to explore TV audience rises from the principles of viewers in accordance with the criteria of audience evaluation. In principle, the rating of TV channels gives you nformation about the level of its activity. Every television channel, television program and even television projection, which should be presented to the audience, should have a target audience. Because, as a result of the implementation of the func tions of television journalism, the channel can meet the needs of the target audience and satisfy their wishes. As a result, you can reach a large audience, regardless of age, social group. It is essential to study the television audience, in particular the target television audience, for a consistent and systematic solution. To identify the structural features and quality indicators of the television audience, the author conducts special surveys and provides detailed diagrams for omestic TV channels, such as “Kazakhstan”, “Khabar”, “31 Channel”, “CPC”, “24 Khabar”. It also highlights some of the modern image of television reporters and classifies their typical shortcomings in their speech culture and provision of information.